Effect of altered gastric emptying and gastrointestinal motility on metformin absorption - Marathe, Punit H.; Wen, Yandong; Norton, Jean; Greene, Douglas S.; Barbhaiya, Rashmi H.; Wilding, Ian R. (British journal of clinical pharmacology, 2000)
Aims The purpose of this in vivo human study was to assess the effect of altered gastric emptying and gastrointestinal motility on the absorption of metformin in healthy subjects. Methods An open‐label, three treatment, three period crossover study was conducted in 11 healthy volunteers. Each subject received 550 mg metformin hydrochloride in solution alone; 5 min after a 10 mg i.v. dose of metoclopramide; and 30 min after a 30 mg oral dose of propantheline. Metformin solution was radiolabeled by the addition of 99mTc‐DTPA. The gastrointestinal transit of the solution was monitored by gamma scintigraphy and the pharmacokinetic data were correlated with the scintigraphic findings. Results Scintigraphic data indicated that pretreatment with metoclopramide decreased gastric emptying time and increased gastrointestinal motility while pretreatment with propantheline had the opposite effect. The systemic disposition of metformin was not altered by pretreatment with metoclopramide and propantheline, as judged by unchanged renal clearance and elimination half‐life of metformin. Extent of metformin absorption was essentially unchanged after pretreatment with metoclopramide. However, AUC(0,∞) and % UR (percent dose excreted unchanged in urine) generally increased with increase in gastric emptying time and small intestinal transit times. GI overlay plots showed that the absorption phase of metformin plasma profile always coincided with gastric emptying and the beginning of decline of metformin plasma concentrations was usually associated with the colon arrival. Only in cases where the intestinal transit was drastically prolonged by propantheline pretreatment, was a decline in plasma levels observed prior to colon arrival. Conclusions Metformin is primarily absorbed from the small intestine. The extent of metformin absorption is improved when the gastrointestinal motility is slowed. These findings have significant implications in the design of a metformin modified release dosage form.